Comportamiento fisiológico del cantiliver en implantología oral - Olave Bustamante, Gilberto; Rueda García, Adriana (Revista Estomatología, 1999)
This paper makes a review as well as an analysis about the type of rehabilitation using the cantilever principle, its physiologic behavior when it is applied upon natural teeth or upon osseointegrated implants. Since the initial works made by Sweden group, the principal and widely used rehabilitation scheme was the cantilever upon implants on the anterior zone or maxilla or mandible. There is no discussed about the success rate obtained using this principle, even though it is going against the basic rules of the conventional fixes prosthesis. It is defined some concepts regarding area, strength and masticatory efficiency in order to understand what is happening with this type of rehabilitation. The results of some publications are also summarized.